Tolerability and psychological effects of a multimodal day-care rehabilitation program for persons with Huntington's disease - Karin Ringqvist; Kristian Borg; Marika C. Möller (Medical Journals Sweden, 2021)
Objective: To determine whether the psychological benefits of intense, inpatient, multimodal rehabilitation for persons with Huntingtons disease (HD), as found in earlier studies, also apply in a shorter, day-care setting. Design: Prospective, non-randomized cohort study. Subjects: Twenty patients attending a group-based 8-week (3 days/week) rehabilitation programme aimed at persons in early stages of HD. Methods: An explorative cohort study on register data from a specialized rehabilitation centre, includ-ing descriptive data, number of cancellations, a self-reported evaluation, and measures of psychiatric symptoms, health-related quality of life, sense of coherence and physical function at baseline and at the end of rehabilitation. Results: Patients' attendance rate was almost 90%. Patients were satisfied, and displayed significantly reduced anxiety and depression and improved health-related quality of life after rehabilitation. Baseline measures of sense of coherence showed significant negative correlation with the number of cancelled days of rehabilitation. Physical function improved, but did not correlate significantly with psychological outcome measures. Conclusion: These results indicate that an 8-week multimodal day-care rehabilitation programme can be tolerable, reduce psychiatric symptoms, and improve health-related quality of life for people with HD. A higher sense of coherence seems to promote attendance rates. Further larger studies, including the impact of cognition and disease progression on the treatment effect, are warranted.